Exercise May Ameliorate the Detrimental Side Effects of High Vitamin D Supplementation on Muscle Function in Mice. (11th March 2020) - Debruin, Danielle A; Timpani, Cara A; Lalunio, Hannah; Rybalka, Emma; Goodman, Craig A; Hayes, Alan
ABSTRACT: Vitamin D is commonly prescribed to normalize deficiencies and to treat osteoporosis. However, the effect vitamin D supplements have on skeletal muscle health is equivocal. Although vitamin D is known to play a role in the various processes that maintain muscle integrity and function, recent studies utilizing high bolus dose vitamin D supplementation has demonstrated an increased risk of falls. Thus, the aim of this study was to investigate the effects of high vitamin D supplementation on skeletal muscle function with and without exercise enrichment. Four‐week old C57BL/10 mice ( n = 48) were separated into either normal vitamin D (1500 IU/kg diet; unsupplemented) or high vitamin D (20, 000 IU/kg diet; supplemented) treatment groups. Each dietary group was further separated into interventional subgroups where mice either remained sedentary or received exercise‐enrichment for 8 weeks in the form of voluntary running. Following the intervention period, whole body in vivo and ex vivo contractile analysis were performed. High vitamin D supplementation decreased force production in the slow‐twitch soleus muscles of sedentary mice ( p < .01); however, exercise normalized this effect. Eight weeks of exercise did not improve fatigue resistance of the extensor digitorum longus (EDL) or soleus muscles in unsupplemented mice, likely due to low levels of activation in these muscles. In contrast, fatigability was improved in the EDL ( p < .01) and even more so in the soleus ( p < .001) in the supplemented exercise‐enriched group. Our data highlights that increasing vitamin D levels above normal reduces postural muscle force as seen in the soleus. Thus, unnecessary vitamin D supplementation may contribute to the increased risk of falls observed in some studies. Interestingly, when vitamin D supplementation was combined with exercise, force production was effectively restored, and fatigue resistance improved, even in muscles lowly activated. Regular exercise may modulate the effects of vitamin D on skeletal muscle, and be recommended for individuals receiving vitamin D supplements. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.